2006
DOI: 10.1158/1055-9965.epi-06-0470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parity on Pregnancy Hormonal Profiles Across Ethnic Groups with a Diverse Incidence of Breast Cancer

Abstract: Epidemiologic evidence suggests that a full-term pregnancy may affect maternal risk of breast cancer later in life. The objective of this cross-sectional study was to compare circulating levels of maternal hormones affecting breast differentiation (human chorionic gonadotropin and prolactin) and proliferation [A-fetoprotein, insulin-like growth factor I (IGF-I), and estradiol] between women at a low to moderate risk (Asians and Hispanics), as compared with women at a high risk for breast cancer (Caucasians and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 45 publications
9
44
2
1
Order By: Relevance
“…Descriptive data characterising the hormonal profile of the entire pregnancy are lacking with regard to parity. The elevated first trimester oestradiol we observed in first compared with subsequent pregnancies has also been shown for the second (Wuu et al, 2002;Arslan et al, 2006) and early third trimesters (Wuu et al, 2002), but perhaps not at delivery (Troisi et al, 2003). The elevated prolactin concentrations in our data for first pregnancies have also been noted in the second trimester (Xu et al, 2003;Arslan et al, 2006), but not later in the pregnancy (Xu et al, 2003), and the first trimester androgen elevations have not been shown at delivery (Troisi et al, 2003).…”
Section: Discussionsupporting
confidence: 72%
“…Descriptive data characterising the hormonal profile of the entire pregnancy are lacking with regard to parity. The elevated first trimester oestradiol we observed in first compared with subsequent pregnancies has also been shown for the second (Wuu et al, 2002;Arslan et al, 2006) and early third trimesters (Wuu et al, 2002), but perhaps not at delivery (Troisi et al, 2003). The elevated prolactin concentrations in our data for first pregnancies have also been noted in the second trimester (Xu et al, 2003;Arslan et al, 2006), but not later in the pregnancy (Xu et al, 2003), and the first trimester androgen elevations have not been shown at delivery (Troisi et al, 2003).…”
Section: Discussionsupporting
confidence: 72%
“…In mid-pregnancy, maternal estriol is elevated in Asian-Americans compared with Caucasians, African-Americans, and Hispanic-American women (53), although no differences were observed for the more biologically active estrogen estradiol in a study of Asian-Americans (mainly second generation) and Caucasians (54). Results for cord hormone concentrations are consistent with higher estriol in Asian-Canadians than Caucasians (55), and no significant differences in estradiol and estrone (44), although the latter data derive from a study of Asian-Americans that were likely to be highly acculturated.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%
“…However it is also possible that lower testosterone levels among parous women are indicative of a more general suppression of ovarian function, which could include modulation of estradiol and progesterone as well. Only a handful of studies have examined these hormones in relation to parity, and most, but not all, reported that estrogen is lower in parous than nulliparous women, adjusting for age and other covariates (26, 28, 32-34). …”
Section: Introductionmentioning
confidence: 99%